2020
DOI: 10.1111/ppc.12673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nonviolent communication‐based training program for inpatient alcoholics in South Korea

Abstract: Purpose: This study aimed to evaluate a communication skills program based on nonviolent communication targeted on inpatient alcoholics at the alcoholics specialized ward.Design and Methods: The sample for this mixed methods quasi-experimental study comprised 47 patients who were hospitalized in the alcoholic wards of two psychiatric hospitals in South Korea. Findings:The program effectively improved participants' empathy, anger expression, communication competence, and alcohol abstinence self-efficacy (p < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
5
1
Order By: Relevance
“…Next, the NVC-CST program did not affect the participants’ anger expression, which is inconsistent with previous results showing that NVC positively changed the anger expression of inpatients receiving treatment for alcohol use disorder [ 23 ]. This may be attributable to differences in the study samples.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Next, the NVC-CST program did not affect the participants’ anger expression, which is inconsistent with previous results showing that NVC positively changed the anger expression of inpatients receiving treatment for alcohol use disorder [ 23 ]. This may be attributable to differences in the study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, instructing participants to write a short testimony of their experiences while completing the given assignments helped them recognize the positive changes in their conversations, which further strengthened their motivation for learning. In a previous study, engaging in NVC increased one’s self-expression and understanding of others [ 23 ], which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, empathy is a modifiable socio‐cognitive factor [ 61 ], and interventions that improve empathy have been shown to reduce a range of problematic behavior, including intimate partner violence [ 62 ], bullying [ 63 ] and aggression [ 64 ]. In fact, a recent study found that an intervention that increased empathy resulted in better alcohol abstinence self‐efficacy in individuals with AUD [ 65 ]. Therefore, treatments that aim to improve empathic abilities in individuals with AUD may result in better short‐ and long‐term outcomes related to both interpersonal problems and alcohol use.…”
Section: Discussionmentioning
confidence: 99%